HUBUNGAN ANTARA INTENSITAS QUALITY TIME ORANG TUA DENGAN PERKEMBANGAN SOSIAL ANAK DI TAMAN KANAK-KANAK KEMALA BHAYANGKARI 02 PADANG - Putri, Dirgahayuni; Suryana, Dadan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the relationship between the intensity of parent–child quality time and children's social development at Kindergarten Kemala Bhayangkari 02 Padang. This research is motivated by the important role of parents in supporting early childhood social development through interactions during quality time activities. The study employed a quantitative approach with a correlational method. The population consisted of all children in Kindergarten Kemala Bhayangkari 02 Padang, with a total sample of 32 respondents involving parents and teachers. Data were collected using questionnaires to measure the intensity of parent–child quality time and observation sheets completed by teachers to assess children's social development. The research instruments were tested for validity and reliability, and all items were declared valid and reliable. Data analysis was conducted using Spearman Rank correlation with the assistance of SPSS version 23. The results showed a correlation coefficient of -0.663 with a significance level of 0.000 < 0.05, indicating a significant relationship between the intensity of quality time and children's social development. The negative direction of the relationship suggests that an increase in the intensity of quality time is not always followed by an improvement in children's social development. These findings indicate that quality time is not solely determined by the duration of togetherness, but also by the quality of interaction between parents and children. Therefore, parents need to create responsive, warm, and meaningful interactions to optimally support children's social development.